Evaluating the value of new metro lines using route diversity measures: the case of Hong Kong's Mass Transit Railway system - Chan, H-Y; Chen, A; Li, G; Xu, X; Lam, W (Elsevier, 2021)
The Mass Transit Railway (MTR) serves as the backbone of the Hong Kong public transportation network and continues to be expanded in phases. Nevertheless, occasional but severe disruptions have raised concerns about whether the proposed MTR expansions will benefit the system resilience. To assess the value of each stage of MTR network expansion, it is key to identify the distributive effects of new metro lines on both accessibility and resilience. This paper applies the route diversity index, a relatively new accessibility indicator, to assess the effects of new lines and evaluate their spatial distribution, variation, and changes at nodal, dyadic, and network levels. The results indicate that the effects on accessibility and resilience will differ between each stage of MTR expansion. On the accessibility front, the benefits of reduced travel times and increased route diversity will be successively extended to more districts with each MTR expansion, and the spatial equity will also be improved gradually by the expansion, especially in isolated regions such as the northern and western New Territories. In contrast, on the resilience front, although the overall network vulnerability will be reduced, the vulnerability of certain parts of the network will be increased, which might necessitate additional resources to protect these stations. However, some new lines will reduce this vulnerability and provide a complementary solution to enhance network resilience. Overall, the insights from this study could assist in cost-effective resource allocation and informed decision-making for the prioritization of future railway investments and cost-effective resource allocation.